PELAKSANAAN PROGRAM WAJIB BELAJAR 12 TAHUN DI KOTA PEKANBARU - Mukhamil Irsyad Merlion; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Education is a basic need of the main and important in our lives. Access to education is one of the most important lines in boosting development in all aspects of life, in particular towards the development of intelligence and skills in community in accordance with Act No. 20 of 2003 on the Organization of education. Follow up on Act No. 20 of 2003, the Central Government made compulsory, with the compulsory education renders justice, can be enjoyed throughout the kids at school age in this country. In realizing this compulsory, the Government of the city of Pekanbaru develop equitable access to quality primary education and nine years and a 12-year compulsory education stub supported by means of an adequate infrastructure and energy professional education as well as the improvement of the governance of the education scale national standards.In this research the concept of theory used the author refers to the theory of management according to G.R. Terry, stating that management is the process of planning, organizing, implementing and monitoring. This research uses descriptive method using qualitative data. Then in the collection of data the author uses data collection techniques include observation, interview and documentation.Based on the research results obtained that the implementation of a 12-year compulsory education program in the city of Pekanbaru has not done due to the large number of constraints still faced in the process of its implementation. Pekanbaru City Government should have special rules that define the execution of this program.Keywords: Implementation, Management, Compulsory Education.